The Relationship Between Upright Delivery Positions And The Incidence Of Perineal Tears In Normal Delivery - Astin Nur Hanifah; Risma Risma; Ismiyanti H. Achmad (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Birth position is one factor that can influence the birth process and the risk of complications during labor. Upright birth positions such as standing, sitting, or squatting are believed to utilize gravity to facilitate the birth process. However, this position is also suspected to be associated with the incidence of perineal tears in normal deliveries. This study aims to determine the relationship between upright birth positions and the incidence of perineal tears in normal deliveries. The study used an analytical design with a cross-sectional approach. The study sample consisted of 60 mothers who gave birth normally, selected using a purposive sampling technique. Data were collected through observation and medical record recording. Data analysis used the chi-square test. The results showed that mothers who gave birth in an upright position had a 40% incidence of perineal tears, while those in a non-upright position had a 65% incidence. The statistical test results showed a p value = 0.032 (p < 0.05). It was concluded that there is a relationship between upright birth positions and the incidence of perineal tears in normal deliveries.